A case study of the deep-sea tailings outfall in the tropical south Pacific. Issue 2 (2nd April 2020) - Leung, Albert Tsz Yeung; Hospital, Aurelien; Young, Chris; Potts, Daniel; Stronach, James; Thompson, Allister
Abstract : Deep-Sea Tailings Placement (DSTP) systems have been used at several mines to discharge diluted mine tailings at great depths. DSTP often provides considerable environmental and engineering benefits compared to traditional on-land tailings storage. The key element in the viability of a DSTP system is the ability to discharge mine tailings at sufficient depths and at such a location that a density current is formed that carries the tailings along the seabed to the abyssal ocean, and such that adequate dilution can be achieved and environmental impacts minimized. Depending on the composition of the slurry, sub-sea plumes might also form from the density current at different levels of neutral buoyancy, further diluting the effluent. The engineering, environmental and construction aspects of the deep-sea outfall system are illustrated through a case study of the DSTP outfall system on Woodlark Island in Papua New Guinea, located in the tropical south Pacific.